0
$\begingroup$

Please could someone help me understand how; A + ~AB = A+B Actually, I don't understand how from A + ~AB we arrive at A+B Anyways thanks for helping me in advance!

$\endgroup$
1
$\begingroup$

$$A+A'B=(A+A')(A+B)=1(A+B)=A+B$$

The first step is Distribution: $A+BC=(A+B)(A+C)$

$\endgroup$
0
$\begingroup$

From

$A \lor \bar{A} = T$

$T \lor B = T$

$B = B \land T = B \land (A \lor \bar{A}) = BA \lor B\bar{A}$

we can rewrite

$A \lor B = A \lor BA \lor B\bar{A} = A(T \lor B) \lor B\bar{A} = A \lor B\bar{A}$

In plain English:
Regardless of $B$, $A \lor \bar{A}B$ is true, if $A$ is true. If $A$ is false, the expression is equal to $B$.

$\endgroup$
  • $\begingroup$ thank you as well, I appreciate your disposition. $\endgroup$ – Grammy Jun 17 '17 at 19:59
0
$\begingroup$

I will use $\bar A$ for ~A.

$A + \bar A B = \overline{\overline{A + \bar{A} B}} = \overline{\bar A \cdot \overline{\bar A B}} =\overline{\bar A \cdot(\bar {\bar A} + \bar B)} = \overline{\bar A \cdot (A + \bar B)} = \overline{\bar A \cdot A + \bar A \cdot \bar B} = \overline{0+\bar A \cdot \bar B} = \overline{\bar A \cdot \bar B} = \overline{\overline{A+B}} = A+B$.

We have used De-Morgan's Laws: $\overline{X + Y} = \bar X \cdot \bar Y$ and $\overline{XY} = \bar X + \bar Y$. Also, $0 + X = X$ for any boolean variable $X$, and $\overline X \cdot X = 0$.

$\endgroup$
  • $\begingroup$ Oohh thank you very much, it has really helped me! $\endgroup$ – Grammy Jun 17 '17 at 19:59

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.